Antibiotic Resistance in Fermented Foods Chain: Evaluating the Risks of Emergence of Enterococci as an Emerging Pathogen in Raw Milk Cheese - Celso Raul Silambo Chaves; Acácio Salamandane; Emília Joana F. Vieira; Cátia Salamandane (International Journal of Microbiology)
Fermented foods, particularly fermented dairy products, offer significant health benefits but also present serious concerns. Probiotic bacteria, such as lactic acid bacteria (LAB), found in these foods have been strongly linked to the selection and dissemination of antibiotic resistance genes (ARGs). This study aims to examine the potential risks associated with fermented foods, despite their importance in human nutrition, by analyzing the entire production chain from raw material acquisition to storage. Focusing on cheese production as a key fermented food, the study will investigate various aspects, including dairy farm management, milk acquisition, milk handling, and the application of good manufacturing practices (GMP) and good hygiene practices (GHP) in cheese production. The findings of this review highlight that ARGs found in LAB are similar to those observed in hygiene indicator bacteria like E. coli and pathogens like S. aureus. The deliberate use of antibiotics in dairy farms and the incorrect use of disinfectants in cheese factories contribute to the prevalence of antibiotic-resistant bacteria in cheeses. Cheese factories, with their high frequency of horizontal gene transfer, are environments where the microbiological diversity of raw milk can enhance ARG transfer. The interaction between the raw milk microbiota and other environmental microbiotas, facilitated by cross-contamination, increases metabolic communication between bacteria, further promoting ARG transfer. Understanding these bacterial and ARG interactions is crucial to ensure food safety for consumers.